Impact of Social Media on Current Medical Conferences - Lin, Jennifer An-Jou; Hsu, Angela Ting-Wei; Huang, Jung-Ju; Daniel, Bassem W.; Lee, Che-Hsiung; Kwon, Soo-Ha; Tang, Evelyn Ting-Hsuan; Chu, Cheng-Feng; Chien, Cheng-An Tony; Chuang, David Chwei-Chin; Lu, Johnny Chuieng-Yi; Koshima, Isao; Wang, Zeng-Tao; Hao, Liwen; Chen, Chao; Chang, Tommy Nai-Jen (Journal of Reconstructive Microsurgery, 2019)
Background Medical conferences are forums for research, continuing medical education, and networking. Social media is increasingly used for communication and networking due to its low cost and ability to overcome large distances. This study investigates the impact that social media brings to the current conference system.Methods There are three parts of this study: (1) comparing two similar brachial plexus injuries (BPIs) courses without (2009) and with (2017) social media support, and the participants' feedback; (2) sharing our experiences in the management of the 2018 International Course on SuperMicrosurgery (ICSM) conference; and (3) evaluating the studies from the social media platform International Microsurgery Club (IMC), for the consensus pertaining to social media and conference system.Results With the help of social media, international attendance increased during the 2017 BPI conference compared with the 2009 BPI course (25 nationalities in 2009 vs. 35 in 2017). At least 23% obtained their meeting information through social media. Live surgery was the overall main attraction (79%). The 2018 ICSM meeting revealed that video posts increased attendance; videos that were the most effective in attracting (viewership) were either short or pertained to surgical procedures. Facebook, Messenger, and WeChat smartphone applications were effective for immediate communication and troubleshooting among the participants. From the IMC polls, 78% believe that the social media and the conference complemented each other. 97% attended the conference to update their skills and knowledge.Conclusion Social media is a quick and economic tool in promoting medical conferences and instant messenger systems offer immediate communication amongst associates. Despite the popularity of social media, the conference still has its irreplaceable role. The combination of the conference and the social media enhances the training and education of microsurgeons.
Keywords: social media; Facebook; international microsurgery club; medical education; brachial plexus; international course on super microsurgery